Being Black and Queer in Pariah (2011) and Moonlight (2016) - Tambunan, Shuri Mariasih Gietty; Tunggal, Gertrud Nimas Cemara (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
The representation of race and sexuality particularly African Americans in Hollywood has always been problematic. In its development Hollywood has been including more representations of African-Americans. With New Black Realism, which started in the midst 90s, the African-American communities change the screen with a more empowering portrayal of the community. A common theme is usually focusing on African-American youth in surviving and negotiating with the current issues concerning race. The question to be asked is to what extent do these changes actually challenge stereotypes? By analyzing two Hollywood films, Pariah (2011) and Moonlight (2016), this article looks into the representation of African American LGBTQ characters to see how the films problematize or affirm stereotypes that have been constructed by mainstream Hollywood. By analyzing narrative elements and the cinematography elements, this research reveals even though the films try to negotiate with stereotypes, they eventually affirms how stereotypes of African Americans LGBTQ are still seen in negative way.